Properties of Generalised Lattice Ordered Groups - Parimi Radha Krishna Kishore; Dawit Cherinet Kifetew (LPPM Institut Teknologi Sepuluh Nopember, 2021)
A partially ordered group (po-group) is said to be a generalised lattice ordered group (gl-group) if the underlying poset is a generalised lattice. This paper is a study of some properties of finite subsets of a generalised lattice ordered group (gl-group). Finally obtained a lattice ordered group (l-group) from the given interally closed gl-group and concluded that every integrally closed gl-group is distributive.